2019
DOI: 10.1093/scan/nsz029
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between oxytocin receptor gene and intergroup relationship on empathic neural responses to others’ pain

Abstract: Empathic neural responses to others’ suffering are subject to both social and biological influences. The present study tested the hypothesis that empathic neural responses to others’ pain are more flexible in an intergroup context in G/G than A/A carriers of the oxytocin receptor gene (OXTR) (rs53576). We recorded event-related brain potentials to painful vs neutral expressions of Asian and Caucasian faces that were assigned to a fellow team or an opponent team in Chinese carriers of G/G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 67 publications
0
11
0
2
Order By: Relevance
“…Another study (Luo et al, 2019) tested the hypothesis that empathic neural responses to others’ pain are more flexible in G/G than A/A carriers (rs53576) of the oxytocin receptor gene (OXTR). They found that G/G carriers showed greater neural responses, over the frontal cortical region, to painful vs. neutral face expressions.…”
Section: Neurobiological and Physiological Correlatesmentioning
confidence: 99%
“…Another study (Luo et al, 2019) tested the hypothesis that empathic neural responses to others’ pain are more flexible in G/G than A/A carriers (rs53576) of the oxytocin receptor gene (OXTR). They found that G/G carriers showed greater neural responses, over the frontal cortical region, to painful vs. neutral face expressions.…”
Section: Neurobiological and Physiological Correlatesmentioning
confidence: 99%
“…Specifically, based on the framework of inherited differential susceptibilities to environmental factors, individuals carrying specific genotypes may be especially vulnerable to adverse environments (Belsky & Pluess, 2009;Luo et al, 2015Luo et al, , 2016. Indeed, studies have examined the effects of gene-environment interactions on individual-level psychological features, such as resilience, empathy, externalizing behavior, and temperament (Caspi et al, 2002(Caspi et al, , 2010Cicchetti & Rogosch, 2012;Das et al, 2011;Luo et al, 2019;Luo, Yu, & Han, 2017;Luo, Zhu, et al, 2017;Thompson et al, 2012). For instance, Cicchetti and Rogosch (2012) combined four genotypes (for the genes encoding serotonin, corticotropin-releasing hormone, dopamine, and oxytocin genes) into a composite score that predicted the resilience levels of low-income maltreated and non-maltreated children.…”
Section: Introductionmentioning
confidence: 99%
“…rs53576 genotypes have previously been found to be associated with implicit responses to infant and adult faces, where G/G carriers exhibited a more positive implicit association to ingroup infant faces ( Senese et al, 2017 ). The rs53576 genotype has also been associated with neural responses toward ingroup and outgroup faces where A/A carriers showed significant empathic neural responses for faces with both shared racial and group identity compared to G/G carriers who showed such empathic responses for faces with either shared racial or group identity ( Luo et al, 2019 ), suggesting that OXTR rs53576 may interact with intergroup relationships on prosocial behavior. However, evidence about associations between SNPs and face processing is inconsistent.…”
Section: Introductionmentioning
confidence: 99%